ANALISIS DAYA SAING EKSPOR JASA NEGARA ASEAN - Efrida Tita; Slamet Santoso; Rochmat Aldy Purnomo; Asis Riat Winanto; Choirul Hamidah (Center for Economic Studies Universitas Katolik Parahyangan, 2020)
This research aims to determine the export competitiveness of asean country's service sector’s. The data used to support this research is secondary data in the form of service sector export data, total exports, and Gross Domestic Product (GDP) Constant Price for the study period in 2015-2019. The analysis tools used are Klassen Typology, Location Quotient (LQ), Revealed Competitive Advantage (RCA), and Overlay analysis. Based on the results of overlay analysis by combining three analytical tools (Klassen Typology, LQ, and RCA), shows that the export competitiveness of the service sector owned by Singapore is insurance and pension services; charges for the use of intellectual property; telecommunications, computer, and information services; and other business services. Malaysia's export competitiveness of the service sector is personal, cultural, and recreational services, while the Philippines is telecommunications, computer, and information services. Meanwhile, Indonesia and Vietnam are ASEAN countries that do not have export-competitive service sectors.